Les friches touristiques dans la moyenne montagne auvergnate, entre effet de cycle et fragilité territoriale - Michel Lompech; Daniel Ricard (Revue de Géographie Alpine)
The article investigates tourist wastelands in Auvergne’s mid-mountain region. They are the product of a complex and regressive process over the medium or long term and have to be looked at within the context of how this tourism was approached and the difficult integration to compete with other tourism-oriented territories from the 1960s. The analysis demonstrates the complexity of explanatory factors such as retail configurations. These factors pose a challenge to the tourism dynamics, the specific location of these mid-mountains, which are often fragile environments, and the attitude of the actors (entrepreneurs, local authorities etc.). The numerous tourist wastelands are unevenly distributed across the territory, and the article seeks to draw up a typology of them.